Skeletal Muscle Mass Has Stronger Association With the Risk of Hyperuricemia Than Body Fat Mass in Obese Children and Adolescents - Xie, Luyao; Mo, Phoenix K. H.; Tang, Qingya; Zhao, Xuan; Zhao, Xuelin; Cai, Wei; Feng, Yi; Niu, Yang (Frontiers in Nutrition, 2022)
Background Hyperuricemia has been increasing among children with obesity in recent years. However, few studies in such a study group had explored the relationship between obesity-anthropometric indexes and hyperuricemia. This study aimed to examine the associations between hyperuricemia and different body components in children and adolescents with obesity, and further explore gender differences in these associations. Methods In this cross-sectional study, a total of 271 obese children and adolescents (153 boys and 118 girls) aged 6–17 years were recruited from Shanghai Xinhua Hospital. Data about basic information, anthropometric assessments, body composition, and laboratory tests of participants were collected. Results In this study, 73 boys (47.71%) and 57 girls (48.31%) were diagnosed to have hyperuricemia. The impacts of percentage of skeletal muscle (PSM) (OR = 1.221, P < 0.001) and skeletal muscle mass (SMM) (OR = 1.179, P < 0.001) on the risk of hyperuricemia was the largest, followed by hip circumference (HC) (OR = 1.109, P < 0.001), waist circumference (WC) (OR = 1.073, P < 0.001), and body fat mass (BFM) (OR = 1.056, P < 0.05) in whole sample, which was adjusted for age, gender and body mass index (BMI). After being stratified by gender, PSM (boys: OR = 1.309, P < 0.001) and SMM (boys: OR = 1.200, P < 0.001; girls: OR = 1.147, P < 0.05) were still the most predictors of hyperuricemia, followed by HC (boys: OR = 1.147, P < 0.001; girls: OR = 1.080, P < 0.05). WC showed a significant association with hyperuricemia only in boys (OR = 1.083, P < 0.05), while BFM showed no association with hyperuricemia in both gender groups after adjusting for age and BMI. Conclusion Our findings suggested that SMM was a stronger predictor of hyperuricemia than BFM in children and adolescents with obesity, especially in boys.